Brewing science, technology and print, 1700-1880 - Sumner, James (James Brinton) (Science and culture in the nineteenth century ;, 2013)
How did the brewing of beer become a scientific process? Sumner explores this question by charting the theory and practice of the trade in Britain and Ireland during the eighteenth and nineteenth centuries.